Open innovation: Membangun kolaborasi dan meningkatkan kreativitas dalam pengembangan produk dan layanan - Alifiyah, Azzahra Lulu (Maliki Interdisciplinary Journal, 2024)
This article discusses the concept of open innovation as an innovative strategy to build collaboration and enhance creativity in product and service development. In an era of intensifying business competition and rapid technological change, open innovation is becoming an increasingly relevant approach to drive sustainable innovation. This article discusses the benefits of open innovation in enhancing creativity and collaboration, and identifies factors that support and hinder the implementation of open innovation. The results show that open innovation can be an effective strategy to improve a company's competitiveness by encouraging greater creativity and collaboration.